Comprehensive Rehabilitation of the Elderly Post-COVID-19: A Multidisciplinary Challenge in the Face of Physical and Psychological Sequelae - Romero-Rodríguez, María Gabriela; Procel-Niama, Cristina Alessandra; Granizo-Lara, Lilian Verónica; Pérez-García, María Belén (Iatreia)
COVID-19 is a multi-organ infectious disease that triggers a severe and highly catabolic inflammatory state. Older adults, particularly those in a state of fragility and with pre-existing conditions, are more susceptible to contracting the disease and developing severe symptoms, which may result in long-term limitations or disabilities. This article outlines the challenges associated with the rehabilitation of elderly patients post-COVID-19. It does so by analyzing the long-term observed physical and psychological sequelae and reviewing various rehabilitation approaches proposed by experts. A search for scientific information was conducted using the PubMed search engine, applying the authors’ criteria for selecting relevant content. The primary challenge in the comprehensive rehabilitation of the elderly post-COVID-19 is the implementation of a multidisciplinary approach that includes early patient assessment to prevent health issues arising from multimorbidities and the state of dependence, fragility, and vulnerability characteristic of these patients. This approach should encompass not only early physical and cardiopulmonary rehabilitation but also psychological support, thereby promoting the independence of the elderly and improving their quality of life within society.